Islamophobia and Acts of Extremism Against Muslim Minorities in Sri Lanka Before and During the Covid-19 Pandemic - Mujahidin, Muhammad Saekul (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Sri Lanka has witnessed many examples of anti-Muslim sentiment and violence since the end of the civil war, especially in 2014 when an ethnic outbreak affected large numbers of people. Sinhala monks and Buddhists appear to have played an important role in covering it. Long wars and ethnonationalist ideology have resulted in a politico-religious shift related to ÔÇ£Buddhist extremismÔÇØ, which engages in embracing and attacking Muslims. This study uses the